An overview of ExReps system - Tanaka, Jiro; Ohta, Yukiko; Matono, Fumio (1989)
Abstract: "An overview of an experimental reflective programming system (ExReps) is presented in this paper. ExReps consists of two layers, i.e., abstract machine layer and execution system layer. Both layers are constructed based on enhanced metacall mechanism. Actual program execution examples and reflective programming examples are also presented."
Keywords: Computer programming